Exchange rate management in emerging markets : intervention via an electronic limit order book - Michael Melvin; Lukas Menkhoff; Maik Schmeling (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper describes and analyzes the implementation of a crawling exchange rate band on an electronic trading platform. The placement of limit orders at the central bank's target rate serves as a credible policy statement that may coordinate beliefs of market participants. We find for our sample that intervention increases exchange rate volatility (and spread) for the next minutes but that intervention days show a lower degree of volatility (and spread) than non-intervention days. We also show for intraday data that the price impact of interbank order flow is smaller on intervention days than on non-intervention days. These stabilizing effects, however, rely on the conditions of large currency reserves and the existence of capital controls; an electronic market seems to support this goal.
Keywords: F39; G15; 330; exchange rates; intervention; microstructure; Wechselkurspolitik; Stufenflexibilität; Devisenmarkt; Börsen-Informationssystem; Mikrostrukturanalyse; Aufstrebende Märkte; Russland